The legacies of the Sokoto Caliphate in contemporary Nigeria - Buba, Malami (History compass, 2018)
Contemporary Nigeria is a product of multiple historical experiences dating back to the antiquities. The nation's uncommon diversity of language, culture, and religion are mostly encapsulated in the foundation and continuing relevance of the Sokoto Caliphate, an Islamic polity founded on the principles of reform and restoration by Usman Dan Fodio in 1804. In this article, I explore how this immense geographical entity of intercontinental resonance was governed, and the lessons of history that Nigeria can draw from its success and tribulation.